Bilateral retinal vasculitis presenting as the first manifestation of systemic lupus erythematosus: a case report - Chirath Priyanga Madurapperuma; Thuvarakan Poobalasingam; Melina Dissanayake; Supul Banagala; Sivatharsini Nagarajah; Bhatiya Premaratne; Keembiyage Ranasiri Dayawansa; Monika De Silva; Harindra Karunatilake (Journal of Medical Case Reports)
Abstract Background Systemic lupus erythematosus is a chronic autoimmune multisystemic disease in which ocular manifestations occur in up to one-third of patients. Although retinal vasculitis is a recognized feature of systemic lupus erythematosus, it is extremely rare to present as the first manifestation. This report describes a rare case of systemic lupus erythematosus, characterized by bilateral retinal vasculitis presenting as the first manifestation, which was subsequently complicated by lupus nephritis. Case presentation We report the case of a 32-year-old female patient from Sri Lanka who presented with progressive visual impairment, followed by fatigue, malaise, and arthralgia. She was initially diagnosed with retinal vasculitis. Later, she developed constitutional symptoms followed by mucocutaneous and renal manifestations consistent with systemic lupus erythematosus. Laboratory findings supported the diagnosis of systemic lupus erythematosus with positive antinuclear antibody and anti-double stranded DNA, as well as low complement levels. Renal biopsy confirmed class III lupus nephritis. The patient received treatment with corticosteroids, mycophenolate mofetil, and hydroxychloroquine, which resulted in significant improvements in visual, renal, and other clinical symptoms. Conclusion It is important to consider systemic lupus erythematosus in the differential diagnosis of isolated retinal vasculitis, even in the absence of its classic symptoms. Early identification through improved diagnostic tools and revised criteria could facilitate timely intervention and improve patient outcomes.